Hubungan antara Konsep Diri dengan Perilaku Konsumtif terhadap Pakaian pada Siswa Kelas IX SMA Muhammadiyah 1 Palembang - Oktarina Moulina; Dwi Despiana (Indonesian Journal of Behavioral Studies, 2021)
This study aims to determine the relationship between self-concept and consumptive behavior in class XI students of SMA Muhammadiyah 1 Palembang totaling 172 students. Data collection uses a self-concept scale and a consumptive behavior scale. This study uses correlational quantitative methods with pearson's product moment analysis. The results of the study revealed that there was a significant negative relationship between self-concept and consumptive behavior in Class XI SMA Muhammadiyah 1 Palembang, this was evidenced by the correlation coefficient r= -0.464 (p<0.01), meaning that the lower the self-concept, the higher the self- concept. high consumptive behavior, on the contrary, the higher the self-concept, the lower the consumptive behavior in students.